The antiviral effect of metformin on zika and dengue virus infection - Carlos Noe Farfan-Morales (Nature Portfolio, 2021)
Abstract The Dengue (DENV) and zika (ZIKV) virus infections are currently a public health concern. At present, there is no treatment or a safe and effective vaccine for these viruses. Hence, the development of new strategies as host-directed therapy is required. In this sense, Metformin (MET), an FDA-approved drug used for the treatment of type 2 diabetes, has shown an anti-DENV effect in vitro by activating AMPK and reducing HMGCR activity. In this study, MET treatment was evaluated during in vitro and in vivo ZIKV infection and compared to MET treatment during DENV infection. Our results demonstrated that MET has a broad in vitro antiviral spectrum. MET inhibited ZIKV infection in different cell lines, but it was most effective in inhibiting DENV and yellow fever virus (YFV) infection in Huh-7 cells. However, the drug failed to protect against ZIKV infection when AG129 immunodeficient mice were used as in vivo model. Interestingly, MET increased DENV-infected male mice's survival time, reducing the severe signs of the disease. Together, these findings indicate that, although MET was an effective antiviral agent to inhibit in vitro and in vivo DENV infection, it could only inhibit in vitro ZIKV infection.